SLATS Truck Theft Data of New York City, 1976-1980 - Gibbs, John J. ([Verlag nicht ermittelbar], 1984)
This data collection is one of three quantitative databases comprising the Commercial Theft Studies component of the Study of the Causes of Crime for Gain, which focuses on patterns of commercial theft and characteristics of commercial thieves. This data collection examines the methods used to commit various acts of theft that involved a truck or the contents of a truck. These data were collected from the files of a specialized New York City Police Department detective squad called the Safe, Loft, and Truck Squad (SLATS), which was created specifically to investigate commercial truck thefts. The variables include type and value of stolen property, weapon involvement, treatment of driver and helper, suspect characteristics, and recovery information.